SISTEM PENDUKUNG KEPUTUSAN KELAYAKAN PEMBERIAN PINJAMAN KEPADA ANGGOTA KOPERASI PRIMA SEJAHTERA UNIT II JAMBI - Ahmad Louis (JURNAL AKADEMIKA)
Decision support systems are part of computer-based information systems (including knowledge-based systems) used to support decision making within an organization or company. It can also be said to be a computer system that processes data into information to take decisions from a semi-structured problem that is a specification